2011
DOI: 10.1016/j.juro.2011.03.106
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Focality Does Not Predict Biochemical Recurrence After Radical Prostatectomy in Men With Clinically Localized Prostate Cancer

Abstract: In this study tumor focality failed to predict patients likely to experience biochemical failure. Tumor characteristics were similar regardless of focality. However, unifocal tumors had smaller volume and were more commonly seen as clinically insignificant compared to multifocal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A previous report indicated that tumor focality can significantly influence the BCR-free survival rate [31]. However, more-recent reports indicated that tumor focality did not predict the risk of BCR after an RP in men with clinically-localized PCa, even if the tumor involved both lobes of the prostate [32], suggesting that tumor focality might not be a suitable predictive marker for BCR in patients with organ-confined PCa. Our study observed that p-Akt expression level should be a better predictive marker of BCR in this PCa population.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated that tumor focality can significantly influence the BCR-free survival rate [31]. However, more-recent reports indicated that tumor focality did not predict the risk of BCR after an RP in men with clinically-localized PCa, even if the tumor involved both lobes of the prostate [32], suggesting that tumor focality might not be a suitable predictive marker for BCR in patients with organ-confined PCa. Our study observed that p-Akt expression level should be a better predictive marker of BCR in this PCa population.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocality remains the most common pattern of disease distribution, with solitary lesions occurring in 13% of patients [14][15][16]. The random sampling that is routinely implemented samples less than 1/1000th of the prostate volume.…”
Section: Editorialmentioning
confidence: 99%
“…Review of biopsy findings suggests that the expected number of cases with unifocal disease may be in the range of 13%–35% 53,54. Of those with low-risk unifocal disease, only 1% displayed extracapsular extension 55.…”
Section: Selection Of Appropriate Patientsmentioning
confidence: 99%